Modeling the galvanic corrosion behavior of PdCu couple used in hydrogen purification – PEM fuel cell hybrid systems. (7th December 2016) - Al-Hadeethi, Farqad F.; Alsyouri, Hatem M.; Dwairi, Sohaib A.
Abstract: Modeling the corrosion behavior of Pd/Cu couple in acidic media (0.25 M HCl) at various operating conditions [(30, 50 °C) and (0, 300, 600, 900 RPM)] was considered as an ultimate goal of this work. Multiple regression analysis with respect to ANOVA was utilized to generate a mathematical correlation. The derived correlation and the surface response revealed that increasing temperature and speed of agitation affected the corrosion rate of Cu in the Pd/Cu couple. This result indicates that using copper in the hydrogen purification – Proton Exchange Membrane (PEM) fuel cell hybrid systems is not acceptable due to the degradation that might occur as a direct result from the galvanic action between Pd/Cu couple. In order to improve the resistance of Pd against corrosion and hydrogen embrittlement at elevated temperatures, it should be alloyed with Au or Ag rather than copper. Highlights: Modeling the corrosion behavior of Pd/Cu in acid at various operating conditions. Interaction among corrosion rate, temperature and speed of agitation was observed. Cu is not recommended as an alloying element with Pd in hydrogen purification.